Xylooligosaccharide Enriched Yoghurt: Physicochemical and Sensory Evaluation - Mumtaz, Semee; Salim-Ur-Rehman; Huma, Nuzhat; Jamil, Amer; Nawaz, Haq (Pakistan Journal of Nutrition, 2008)
Enrichment of yoghurt with xylooligosaccharide (XO) at different levels was studied with physicochemical and sensory analysis. Yoghurt prepared by incorporation of XO were compared for these characteristics to the yoghurt containing stabilizer (gelatin, 0.4% w/w) in addition to XO. Moisture contents, pH, acidity and total solids were studied. These attributes were significantly affected by the use of stabilizer and rate of XO incorporation. Use of gelatin produced better results in terms of lowering syneresis and improved appearance, body and texture. Addition of XO upto 3.5% did not influence taste and overall acceptability but higher levels contributed aftertaste.